KONTRIBUSI DAN PERTUMBUHAN PEMBIAYAAN BANK SYARIAH DI INDONESIA BERDASARKAN JENIS AKAD PERIODE TAHUN 2008-2013 - ROMI ISKANDAR (Universitas Islam Negeri Imam Bonjol Padang, 2016)
The research theme is the concept of business according to Islamic economics. This study aims to describe how to financing of Islamic Bank contract performance 2008 -2013 period. This research base on published data of Bank Indonesia and Financial Service Autority. The method used in this research is ratio analysis tehcnic and Coomonsize analysis technic of the quantitative approach. The result shows that:signifcant contribution of murabaha and musyaraka contract financing in Islamic Bank balance statements, significant and smoth of growth level with murabaha and musyaraka contract. The impact of this research, Islamic Bank must be focus to use of murabaha and musyaraka contract financing and salam contract,istishna contract, ijarah contract unimplemented or maybe deleted. Because its unsignificant countribution and more fluktuatif performance of growth.